Effectiveness of Short-term Dynamic Mentalization-based Therapy on Maternal Reflective Capacity and the Mother-Child Relationship - Darabi, Tanya; Amini, Naser; Keykhosrovani, Mouloud (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to assess the effectiveness of short-term dynamic mentalization-based therapy on maternal reflective capacity and the mother-child relationship. Methods and Materials: The research design was a quasi-experimental pre-test, post-test with a control group. The population consisted of all mothers with children aged 2 to 6 who attended counseling centers in Ahvaz in the year 2023. Forty participants were selected from this population using a convenience sampling method. From these, two groups of twenty were randomly formed, one as the intervention group and the other as the control group. The intervention protocol used was based on the short-term dynamic mentalization-based therapy protocol by Mousavi and Bahrami (2020). Data were collected using the Parental Reflective Functioning Questionnaire by Luyten et al. (2017) and the Mother-Child Relationship scale by Robert M. Ross (1961). Data analysis was conducted using descriptive and inferential statistics (analysis of covariance). Findings: Results from the analysis of covariance, adjusted for pre-test effects, showed significant differences between the experimental and control groups in terms of maternal reflective capacity and its components, and the mother-child relationship. The results indicated that the intervention improved both maternal reflective capacity and the mother-child relationship. Conclusion: Based on the findings of this study, it can be concluded that short-term dynamic mentalization-based therapy can serve as an effective therapeutic method for enhancing maternal reflective capacity and the mother-child relationship in counseling settings.